2009
DOI: 10.1158/0008-5472.can-08-4512
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of DPAGT1 Leads to Aberrant N-Glycosylation of E-Cadherin and Cellular Discohesion in Oral Cancer

Abstract: Cancer cells are frequently characterized by aberrant increases in protein N-glycosylation and by disruption of E-cadherin-mediated adherens junctions. The relationship between altered N-glycosylation and loss of E-cadherin adhesion in cancer, however, remains unclear. Previously, we reported that complex N-glycans on the extracellular domains of E-cadherin inhibited the formation of mature adherens junctions. Here, we examined whether dysregulated N-glycosylation was one of the underlying causes for cellular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 45 publications
1
83
0
Order By: Relevance
“…Associated with Up-regulation of CTHRC1 Expression-Previously, we reported that aberrantly amplified DPAGT1 leads to hyperglycosylation of E-cadherin and consequently reduced intercellular adhesion (6,20). Recent studies have identified an N-glycoprotein, CTHRC1, as a key regulator of cell motility in cancer (25,26).…”
Section: Augmented Dpagt1 Levels In Human Oscc Specimens Arementioning
confidence: 99%
“…Associated with Up-regulation of CTHRC1 Expression-Previously, we reported that aberrantly amplified DPAGT1 leads to hyperglycosylation of E-cadherin and consequently reduced intercellular adhesion (6,20). Recent studies have identified an N-glycoprotein, CTHRC1, as a key regulator of cell motility in cancer (25,26).…”
Section: Augmented Dpagt1 Levels In Human Oscc Specimens Arementioning
confidence: 99%
“…The Nglycosylation status of E-cadherin has been shown to regulate the molecular organization and cytoskeletal association of Ecadherin protein complexes, known as adherens junctions (AJs) (Jamal et al, 2009;Liwosz et al, 2006;Nita-Lazar et al, 2009;Nita-Lazar et al, 2010). Increased DPAGT1 expression is associated with extensive N-glycosylation of E-cadherin, which precludes its interaction with stabilizing proteins and with the cytoskeleton and promotes the formation of nascent AJs in proliferating and cancer cells (Liwosz et al, 2006;Nita-Lazar et al, 2009;Nita-Lazar et al, 2010). In contrast, downregulation of DPAGT1 expression leads to reduced N-glycosylation of Ecadherin, which is required for the formation of mature AJs in dense cultures and differentiated cells (Nita-Lazar et al, 2010;Vagin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, partial inhibition of DPAGT1 with siRNA results in the production of hypoglycosylated Ecadherin, which organizes mature AJs. In cancer cells, downregulation of DPAGT1 has been shown to reverse their mesenchymal phenotype to an epithelial morphology (Jamal et al, 2012;Nita-Lazar et al, 2009). Likewise, the hypoglycosylated E-cadherin mutant, V13, generated by the deletion of the major complex and high mannose/hybrid Nglycan addition sites, has been shown to form mature AJs in Chinese Hamster Ovary (CHO) cells lacking endogenous Ecadherin (Liwosz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Altered N-glycosylation of proteins has been linked to cancer progression (24,25). Notably, N-glycosylation participates in the adherence of circulating tumor cells to the microvascular bed essential for extravasation and facilitates metastasis from the blood or lymph to other organs (26).…”
mentioning
confidence: 99%